Transcatheter aortic valve implantation: current status and future perspectives. (27th April 2018) - Cahill, T J; Chen, M; Hayashida, K; Latib, A; Modine, T; Piazza, N; Redwood, S; Søndergaard, L; Prendergast, B D
Abstract: In the 16 years since the first pioneering procedure, transcatheter aortic valve implantation (TAVI) has come of age and become a routine strategy for aortic valve replacement, increasingly performed under conscious sedation via transfemoral access. Simplification of the procedure, accumulation of clinical experience, and improvements in valve design and delivery systems have led to a dramatic reduction in complication rates. These advances have allowed transition to lower risk populations, and outcome data from the PARTNER 2A and SURTAVI trials have established a clear evidence base for use in intermediate risk patients. Ongoing studies with an expanding portfolio of devices seem destined to expand indications for TAVI towards lower risk, younger and asymptomatic populations. In this article, we outline recent advances, new devices and current guidelines informing the use of TAVI, and describe remaining uncertainties that need to be addressed.